Unlocking the household ‘Black Box’: a gendered analysis of smallholder farmers' participation in the cassava (Manihot esculenta crantz) value chain in Tanzania - Masamha, Blessing; Thebe, V.; Uzokwe, Veronica N.E. (Wiley, 2018)
Women in developing countries are often omitted from key parts of the agricultural value chains. We used household survey data in bi-probit and ordinary least squares regression models to estimate the determinants of women’s participation in cassava cultivation and marketing in Tanzania. Land size and region, among other factors, were significant determinants of household decisions to grow cassava. Policies for improving women’s land rights and infrastructure would help to promote their participation in cassava production, processing and marketing. Improved methods of delivering extension information would also improve women’s participation in the cassava value chain markets.